Banking in the negative: A vector error correction analysis of bank-specific lending and deposit rates - Alessandra Agati; Michael Sigmund (Oesterreichische Nationalbank (OeNB), 2025)
We analyze the impact of negative reference rates on the interest behavior of more than 500 Austrian banks from 2009Q1 to 2021Q4. Using panel vector error correction analysis with the Engle-Granger procedure in two steps, we establish a cointegration vector that links bank-specific lending rates, deposit rates, the 3-month Euribor, and the ECB Deposit Facility Rate. We propose two hypotheses to evaluate the effects of negative 3-month Euribor on this vector. Firstly, we explore how an Austrian Supreme Court decision enforcing a zero-lower bound on household deposits could decrease the lending-deposit rate spread. Secondly, we examine the emergence of two "true prices" for loans and deposits due to the negative 3-month Euribor. This is linked to an Austrian Supreme Court decision mandating the transmission of negative reference rates to bank-specific lending rates, potentially affecting cointegration with the 3-month Euribor. Our findings show a significant spread reduction after the introduction of negative reference rates, primarily driven by changes in the cointegration relationship between bank-specific lending rates and the 3-month Euribor. Additionally, by including the ECB Deposit Facility in our cointegration model, we capture the direct impact of the Targeted Long-term Refinancing Operations on the lending rate.
Keywords: C33; G21; E58; E43; 330; Interest rate setting; panel cointegration; negative interest rate environment